The Response of High Performance Spring Wheat (Triticum astivam L.) Yield and Its Components to Wide Range of Sowing Dates and Plant Densities - Hussain, Shwana Ahmad; Abdulqader, Shang Haseeb; Mustafa, Kamil Mahmood (Sulaimani Journal for Pure and Applied Sciences, 2018)
A field experiment was conducted to determine the influence of six various seed rates: R1 (120 kg ha-1), R2 (140 kg ha-1), R3 (160 kg ha-1), R4 (180 kg ha-1), R5 (200 kg ha-1), and R6 (220 kg ha-1) and six sowing dates: T1 (Nov-15th), T2 (Dec-5th), T3 (Dec-25th), T4(Jan-15th), T5(Feb -5th), T6(Feb-25th) on yield contributing traits of wheat cultivar Adana-99. Results showed that the effects of date of sowing, seeding rates and its interaction on the all studied yield parameters were significant (P≤0.01). Maximum mean values were recorded for the plant height (cm) in T1 (Nov-15th) with R6 (220 kg ha-1) , spike length (cm) in T1 (Nov-15th) with R1(120 kg ha-1), number of spike m-2 T2 (Dec-5th) with R6 (220 kg ha-1), number of grain spike-1 T1 (Nov-15th) with R1 (120 kg ha-1), 1000 grain weight (g) T1 (Nov-15th) with R2 (140 kg ha-1), and grain yield (ton ha-1) T2 (Dec-5th) with R5 (200 kg ha-1). On the basis of our results, it is concluded that wheat Adana-99 cultivar should be sown between November-15 to Desember-5 with seed rate of 200 kg ha-1 under the guaranteed rainfed areas in Kurdistan- Iraq Region.
Keywords: Wheat; Sowing date; Seeding rate; Yield attributes